2001
DOI: 10.1103/physrevlett.86.4211
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Collapse of a Bose-Einstein Condensate

Abstract: The point of instability of a Bose-Einstein condensate (BEC) due to attractive interactions was studied. Stable 85Rb BECs were created and then caused to collapse by slowly changing the atom-atom interaction from repulsive to attractive using a Feshbach resonance. At a critical value, an abrupt transition was observed in which atoms were ejected from the condensate. By measuring the onset of this transition as a function of number and attractive interaction strength, we determined the stability condition to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
426
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(460 citation statements)
references
References 24 publications
32
426
1
1
Order By: Relevance
“…In the latter, we study the stability of a soliton when the scattering length of the condensate is changed in a controllable way. This study is stimulated by the recent experiments in 85 Rb by Cornish et al [20,21]. Fi-nally we present our conclusions in Section V.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the latter, we study the stability of a soliton when the scattering length of the condensate is changed in a controllable way. This study is stimulated by the recent experiments in 85 Rb by Cornish et al [20,21]. Fi-nally we present our conclusions in Section V.…”
Section: Introductionmentioning
confidence: 87%
“…Since a condensate with positive scattering length is stable, the bright soliton thus created is no longer limited by the collapse of the condensate. Finally, it has been recently shown that with the well-controlled use of Feshbach resonances in 85 Rb, it is possible to make a condensate with attractive interactions in a very controllable way [20,21]. This opens a new way to study bright solitons in matter waves.…”
Section: Introductionmentioning
confidence: 99%
“…implying the existence of a confinement-induced resonance CIR [16,20] of the coupling constant as a s is tuned via a 3D Feshbach resonance [32] past the resonance point a s /a ⊥ = |ζ(1/2)| −1 = 0.6848 . .…”
Section: Spinless Bosonsmentioning
confidence: 99%
“…It was not until 2006 that solitary waves were again investigated experimentally, this time at JILA [11] using the same 85 Rb experiment that has first observed tunable atomic interactions [33] and controlled collapse [15]. This new work concluded that the stable remnant observed previously in the collapse experiments divided into similar solitary wave structures as seen at Rice.…”
Section: Observation Of Bright Solitary Matter Wavesmentioning
confidence: 61%